Entrepreneurship channels and sustainable development: directions for the Asian economy - Cheng, Weichao; Adejumo, Oluwabunmi O. (Journal of Business Economics and Management, 2021)
Entrepreneurship has been identified as a catalyst for creating opportunities and enhancing productivity. The Asian economy is one of the fastest growing economies and entrepreneurially inclined continents of the world, owing to the phenomenal strides of China’s economic activities. Despite these, the region is still characterized as developing in terms equality, real income growth and welfare distributions. Thus, one wonders the extent the entrepreneurial strides impact on the continent; and, to what extent are the socio-economic structures of the Asian economy relevant for achieving sustainable entrepreneurship development.  Thus, by employing the Generalized Method of Moments (GMM), this study assesses the extent to which the current wave of entrepreneurship outcomes can actualize the Global Development Goals slated for 2030. The findings show that improvement in life expectancy and decrease in inequality influenced entrepreneurial outcomes via the basic requirement channel; while higher education which is an efficiency enhancing channel stimulates income than innovations; thus, indicating the need for continuous investments for nascent training; while investments in research and development is an institutional channel that promotes entrepreneurial outcomes. Thus, if the global goals will be actualized, policy makers should strengthen infrastructures and create enabling environments that will improve entrepreneurial outcomes within Asian economies.